"Our burgers eat carbon": Investigating the discourses of corporate net-zero commitments. Issue 142 (April 2023) - Christiansen, Kirstine Lund; Hajdu, Flora; Planting Mollaoglu, Emil; Andrews, Alice; Carton, Wim; Fischer, Klara
Abstract: Corporate net-zero emission pledges have multiplied in recent years, with estimates suggesting that more than 1000 companies have made such commitments. While seemingly indicative of companies stepping up to address climate change, critics have argued that pledges may be mere greenwashing if they rely on excessive offsetting and legitimise business-as-usual. Considerable grey and academic literature has debated the problems of net-zero and explored the integrity and transparency of net-zero plans. We add to this literature by investigating discursive aspects of net-zero logics through an in-depth case study of the Swedish fast food chain MAX Burgers AB. Through a textual analysis of MAX's communication of its 'climate-positive' – or net-negative – burgers, we explore the narratives underpinning its net-zero work and how these serve MAX's interests. Our investigation shows that MAX's net-zero claim justifies its existing business practices and directs focus away from actions that could directly reduce its emissions. Thus, we show that MAX is pushing non-transformative solutions, such as offsetting and voluntary corporate action, while shifting responsibility for climate action onto others, such as consumers and smallholder farmers in the global South. We conclude that even seemingly progressive corporate net-zero pledges and claims become problematic if they distract from real reductions and justify carbon-intensive lifestyles. Highlights: We investigate the net-zero claims and narratives of a Swedish fast food chain. Net-zero claims may serve to justify business-as-usual corporate climate approaches. The claim shifts responsibility to act and proposes non-transformative solutions. Carbon-intensive lifestyles in the global North are enabled and legitimised. Without regulation net-zero pledges risks diverting from decarbonisation efforts.